Development Of Mayangan Fishing Port As A Tourism Object Of Probolinggo City 2012-2019 - Saiful Bahriyanto; Sugiyanto Sugiyanto; Bambang Soepeno; Rully Putri Nirmala Puji; Jefri Rieski Triyanto; Guruh Prasetyo (JURNAL HISTORICA, 2021)
The background of this research is the development of the Mayangan Fishing Port from a fishing port into a tourist attraction. The purpose of this study was to determine the background and process of Mayangan Fishery Port becoming a tourism object in 2012 and the development process as a tourism object in 2012-2019. The method used in this research is the historical method which has four stages, namely heuristics, criticism, interpretation, and historiography. This research was conducted in Mayangan Village, Mayangan District, Probolinggo City in 2019. The results of this research are that since 2012-2019 the Mayangan Fishery Port has carried out various developments in terms of attractions, amenities, and accessibility. The conclusion of this research is Since 2012-2019, the management continued to strive to develop attractions, amenities, and tourist accessibility at the Mayangan fishing port. Suggestions by researchers for managers to focus more on promotion.